Transborder Data Flow and the Protection of Privacy: The Harmonization of Data Protection Law - Cooepr, David M. (Tufts Archival Research Center, 2005)
Volume 8, Issue 2. Summer Recent developments in computer and communications technologies have facilitated the flow of information across national borders. The ease of gathering and transferring data has raised serious questions regarding the protection of the individual from the compilation and misuse of personal information. Governments have an interest in restricting some information flow, hut many businesses depend on the ability to send information freely across borders. In this article, David M. Cooper explores the complexity and variety of interests related to the problem of transborder data flow. He reveals how differing national interests in limiting the flow of data have led to the enactment of significantly different national data-protection and privacy laws in the United States and Europe. After surveying the developments in privacy legislation, Mr. Cooper reviews the recent attempts to harmonize these disparate national laws by implementing international guidelines and conventions. The author concludes by proposing several measures that can be taken by the United States to aid in efforts toward the harmonization of privacy law.